Optimasi Susunan Gizi Makanan Bagi Pasien Rawat Jalan Penyakit Jantung Menggunakan Real Coded Genetic Algorithm (RCGA) - Ratih Diah Puspitasari; Dian Eka Ratnawati; Mochammad Ali Fauzi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Heart is one of the most important organs in the human body. Nowadays, coronary heart disease is one of the diseases that tend to invade a person's heart and dietary arrangements is a must for people who have this kind of disease in order to be healthy like normal people. This research is focused on recommending food nutrition for outpatients who suffers from coronary heart disease that often called diet heart 4. This study, titled optimization arrangement of food nutrition for outpatient using real coded genetic algorithm (rcga), the results that is displayed by the program is patient's data such as age, weight, height and foodstuffs that comply with the needs of the outpatients with the lowest prices of any food. This algorithm consists of an initial population of the initialization stage, the reproduction consisting of crossover and mutation, the calculation of the fitness and selection. The research on using the names of 271 food with nutrient content (source of carbohydrates, a source of protein, vegetable source of protein, vegetables, fruits, snacks, and oil/FAT). From the results of testing, this research obtained optimal parameters of 500 population with average fitness of 12347, 3, 50 generations with average fitness of 11795.8 and the combination of cr = 0 and mr = 0.9. with an average value of fitness 11940.7. The results of the program with the parameter generate an average median difference in actual data - with data from the program of 51.815 or 2.30%.